2022
DOI: 10.1097/mcc.0000000000000952
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter edge-to-edge repair in patients with mitral regurgitation and cardiogenic shock: a new therapeutic target

Abstract: Purpose of reviewCardiogenic shock with significant mitral regurgitation portends a poor prognosis with limited therapeutic options. Herein, we review the available evidence regarding the patient characteristics, management, impact of transcatheter edge-to-edge repair (TEER) on hemodynamics, and clinical outcomes of patients with cardiogenic shock and mitral regurgitation.Recent findingsSeveral observational studies and systematic reviews have demonstrated the feasibility and safety of TEER in cardiogenic shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The physiological effects of percutaneous or surgical repair leads to a reduction of MR subsequently causing a decrease in left atrial pressure, pulmonary arterial pressure, and right ventricular afterload while reducing the LV volume and dilation and increasing forward cardiac output to improve hemodynamic status. 29 Indeed, reverse remodeling of the left ventricle by TEER has been reported. 30 TEER may serve as a salvage therapy in both functional MR and degenerative MR to reduce dependence on inotropes and MCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological effects of percutaneous or surgical repair leads to a reduction of MR subsequently causing a decrease in left atrial pressure, pulmonary arterial pressure, and right ventricular afterload while reducing the LV volume and dilation and increasing forward cardiac output to improve hemodynamic status. 29 Indeed, reverse remodeling of the left ventricle by TEER has been reported. 30 TEER may serve as a salvage therapy in both functional MR and degenerative MR to reduce dependence on inotropes and MCS.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no single etiology for MR, the respective in‐hospital mortality for degenerative and functional MR were similar. The physiological effects of percutaneous or surgical repair leads to a reduction of MR subsequently causing a decrease in left atrial pressure, pulmonary arterial pressure, and right ventricular afterload while reducing the LV volume and dilation and increasing forward cardiac output to improve hemodynamic status 29 . Indeed, reverse remodeling of the left ventricle by TEER has been reported 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe DMR in cardiogenic shock face especially high mortality and morbidity, with limited options for intervention and challenging approaches to pharmacologic and mechanical support. 3 However, mTEER has been less well studied in patients with cardiogenic shock, with the literature mostly limited to case series and observational studies of functional MR. Two recent retrospective studies using data from the STS and American College of Cardiology Transcatheter Valve Therapy Registry and Centers for Medicare and Medicaid Services found that among patients with DMR or functional MR complicated by cardiogenic shock, mTEER can lower in-hospital mortality, 1-year mortality, and number of heart failure admissions by as much as 50%. 4 The first randomized controlled trial, MINOS (Transcatheter Mitral Valve Repair for Inotrope Dependent Cardiogenic Shock), will compare mTEER to medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Dr Jung reviews [9] the increasing recognition of mitral regurgitation (MR) as a potential therapeutic target in select patients with CS. Indeed, as many as 20% of patients with CS have concomitant moderate or greater MR [10].…”
mentioning
confidence: 99%